2015
DOI: 10.3923/jbs.2015.116.123
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Methanol Extract of Abrus precatorius Leaves on Male Wistar Albino Rats Induced Liver Damage using Carbon Tetrachloride (CCl4)

Abstract: A B S T R A C T This study evaluates qualitative and quantitative phytochemical properties ofAbrus precatorius leaves. The vitamins and therapeutic effect of methanol extract against tetrachloride (CCl 4 ) induced liver damage in male Wistar albino rats. The results of phytochemical and vitamins indicates richness in saponins, tannins, alkaloids and flavonoids with value 30.05±0.22%, while vitamins such as thiamine, riboflavin, niacin, antioxidant and vitamins A, C and E was quantified. The liver damage was ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
(28 reference statements)
1
3
0
Order By: Relevance
“…The estimated LD50 of the extracts being greater than 5000 mg/kg suggests that the extract is fairly safe with a very low toxicity. This finding is in agreement with a previous study (26), reporting that the extract of A. precatorius leaves are safe for consumption as no signs of toxicity or death was ever recorded even at a concentration of 500 mg/kg of the extract (26). This is contrary to the findings of Tion et al (1) who reported that the estimated LD50 of the A. precatorius seed extracts to be at doses of 175-187.5 mg/kg.…”
Section: Discussionsupporting
confidence: 91%
“…The estimated LD50 of the extracts being greater than 5000 mg/kg suggests that the extract is fairly safe with a very low toxicity. This finding is in agreement with a previous study (26), reporting that the extract of A. precatorius leaves are safe for consumption as no signs of toxicity or death was ever recorded even at a concentration of 500 mg/kg of the extract (26). This is contrary to the findings of Tion et al (1) who reported that the estimated LD50 of the A. precatorius seed extracts to be at doses of 175-187.5 mg/kg.…”
Section: Discussionsupporting
confidence: 91%
“…The adverse effects of untreated diabetes on the hepatic integrity and functions could have adversely impaired the ability of the hepatic cells to synthesize sufficient proteins including albumin required for various biochemical functions. The very low albumin levels in the diabetic untreated rats could predispose the rats to increased risk of atherosclerosis and cardiovascular disorders due to the inability of insufficient circulating albumin concentration to transport fatty acids including low-density lipoprotein from extra-hepatic tissues to the liver for metabolism as reported by Uroko et al (2015) (Ikechukwu et al, 2015). Contrarily, the substantially raised serum total protein, and albumin and significantly declined levels of conjugated and unconjugated bilirubin in the diabetic rats administered different doses of ABE are attributed to the hepatoprotective property of the extract that protected the liver from adverse hepatic effects of diabetes and maintained improved hepatic functions in the rats.…”
Section: Discussionmentioning
confidence: 95%
“…Polyphenols, flavonoids, β-carotene, glutathione, α-tocopherol, and ascorbic acid were identified from the leaves by Palvai et al (2014). Preliminary phytochemicals such as alkaloids, antraquinones, carbohydrates, flavonoids, glycosides, hydrogen cyanide, oxalate, phenols, phytate, saponin, steroids, tannins, terpenoids, and vitamins such as vitamin E, vitamin A, vitamin C, Niacin, Riboflavin, and Thiamine were recorded from the aerial parts of A. precatorius (Alli et al 2011;Arora et al 2011;Taur and Patil 2011;Shourie and Kalra 2013;Gnanavel and Saral 2013;Marimuthu et al 2014;Bhumi and Savithramma 2014;Ikechukwu et al 2015;Amit et al 2018). Oladimeji et al (2016) isolated 45 essential oil compounds, of which γ-cadinene, α-selinene, α-cubenene, β-caryophyllene, germacrene B, α-copaene and linalool, caryophyllene oxide, β-elemene, and α-caryophyllene are the principal components.…”
Section: Phytochemistrymentioning
confidence: 99%
“…Phytochemicals extracted from various parts of A. precatorius exhibit activities including antitumor (Subba Reddy and Sirsi 1969;Bhutia et al 2009), neuromuscular effects (Wambebe and Amosun 1984), sperm antimotility activity (Ratnasooriya et al 1991), severe diarrhea/significant gastro-intestinal motility activity (Nwodo and Alumanah 1991), Alzheimer's disease (Zambenedetti et al 1998), antianthelmintic (Molgaard et al 2001), anti-inflammatory activity (Anam 2001;Arora et al 2011;Yonemoto et al 2014;Bahtiar et al 2017), alpha-amylase inhibition (Anam 2001;Bahtiar et al 2017), antithrombin (Chistokhodova et al 2002), antimalarial (Limmatvapirat et al 2004;Menan et al 2006), antiepileptic (Moshi et al 2005), immunomodulator (Tripathi and Maiti 2005), antimicrobial (Zore et al 2007), antihypoglycemic, antihypolipidemic (Nwanjo 2008), antifertility (Jahan et al 2009), antidiabetic (Gbolade 2009;Boggula et al 2018), Dalton's lymphoma (Bhutia et al 2009), hepatoprotective activity (Battua and Kumar 2009;Ikechukwu et al 2015), immunostimulatory properties (Maiti et al 2009), nephroprotective (Sohn et al 2009a, b) renal damage (Ae et al 2009;Subrahmanyan et al 2008;Attal et al 2010;Verma et al 2011;Garaniya and Bapodra 2014), antiimplantation activity (Okoko et al 2010), antiasthmatic (Taur and Patil 2011;Taur et al 2017), analgesic potential...…”
Section: Antimicrobial and Other Propertiesmentioning
confidence: 99%